Septic arthritis with osteomyelitis due to Salmonella enterica serotype Dublin: A case series - Jiang, Boyi; Xu, Hong; Zhou, Zongke (Frontiers in Surgery, 2023)
Abstract Background: Septic arthritis with osteomyelitis due to Salmonella enterica serotype Dublin is rare. We reviewed and analyzed cases of septic arthritis with osteomyelitis due to Salmonella enterica serotype Dublin seen at our institution. Methods: The medical records of all patients diagnosed with Salmonella septic arthritis and/or Salmonella osteomyelitis during 2017–2022 were included. We reviewed the diagnosis, medical history, clinical management, and outcome of all cases. Results: Five patients with Salmonella septic arthritis or Salmonella osteomyelitis were identified during the 5-year study period. They were all male; the median age was 53 years (range 15–56). Only one was immunodeficient. All five patients were infected at the hip joint and ipsilateral femur, while two suffered bilateral hip septic arthritis with femoral osteomyelitis. Salmonella Dublin was isolated from the hip joint fluid of all patients. Four presented with fever and constitutional signs within four weeks of symptom onset. Four had positive blood cultures, and only one patient had gastrointestinal symptoms. Four patients underwent surgical debridement as the primary surgical plan, and two underwent secondary two-stage exchange after primary surgical debridement failure. The last patient had a two-stage exchange directly as the first surgical treatment. All patients received intravenous antimicrobial therapy for a median duration of 6 (range 4–12) weeks and oral antimicrobial therapy for a median duration of 4 (range 4–6) weeks. All patients had a median duration of follow-up of 12 months (range 9–25), and none had evidence of recurrence of infection. Conclusions: Septic arthritis due to Salmonella Dublin remains rare. It frequently occurs with ipsilateral femur osteomyelitis adjacent to the infected hip joint in our cases. Surgical debridement or two-stage exchange, along with 4–12 weeks of effective intravenous and followed by 4-6 oral antimicrobial therapy, could successfully eradicate the infection.